Enhancing Multiple Ways of Knowing; Comment on “Evaluating Public Participation in a Deliberative Dialogue: A Single Case Study” - Katherine M. Boydell (International Journal of Health Policy and Management, 2023)
This commentary reviews the Scurr and colleagues’ article published in International Journal of Health Policy and Management in February 2022 on “Evaluating Public Participation in a Deliberative Dialogue: A Single Case Study.” Schur adds to the current knowledge base by extending the stakeholder groups in deliberative dialogues (DD) to members of the affected community, a practice not commonly used in such DD strategies. Their study supports the inclusion of public participants in such dialogues, and offers practical guidelines for ways in which to accommodate these important participants. This commentary highlights the need to acknowledge diverse types of knowing into what is considered evidence and advocates for evidence to include a wide-ranging variety of sources including tacit knowledge via experience and ongoing learning.